Using the job requirements approach and matched employer-employee data to investigate the content of individuals' human capital - Ferran Mane; Daniel Miravet (Journal for Labour Market Research, 2016)
The aim of this paper is to measure the returns to human capital. We use a unique data set consisting of matched employer-employee information. Data on individuals' human capital include a set of 26 tasks that capture the utilization of workers' skills in a very detailed way. Thus, we can expand the concept of human capital and discuss the type of skills that are more productive in the workplace and, hence, generate a higher payoff for the workers. This paper gives evidence that the returns to generic skills differ depending on the position of the worker in the firm. Only numeracy skills are reward independent of the occupational status of the worker. We also show that generic skills and other measures of human capital have independent effects on wages.
Keywords: J24; J31; 330; Bildungsertrag; Arbeitsanforderungen; berufliche Qualifikation; Qualifikationsanforderungen; Produktivitätseffekte; Lohnhöhe; Tätigkeitsmerkmale; Qualifikationsverwertung; Allgemeinbildung; Fachkenntnisse; betrieblicher Status; soziale Qualifikation; Schlüsselqualifikation; Spanien; Katalonien